Planʺ bukhty Bechevinskoĭ sostavlenʺ po glazomi︠e︡rnoĭ sʺemki︠e︡ i promi︠e︡ru Shkhipera Shkhuny "Storozhʺ" F. Geka / Chertilʺ khimich. tushʹi︠u︡ A. Kamarovʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1901)
Relief shown by form lines. Depths shown by soundings.; Main title translation: Map of Bechevinskaya Bay compiled from the survey of the schooner "Storozh" under F. Höök in 1900.; Top margin title translation: Eastern coast of the Kamchatka Peninsula.; "Masshtabʺ 290 sazh. vʺ di︠u︡ĭmi︠e︡" = Scale 290 fathoms in 1 inch.; Coordinates given on map for Bechevinskaya Bay: 53°12'00.0"N 159°53'00.0"E.; "No. 568" -- bottom right margin Color; 1:18,000